Relationships between Total Quality Management Practices, Organizational Culture and Teacher’s Performance: Study from Seventh Day Adventist High Schools in West Indonesia - Sihotang, Ronny Buha; Zebedeus, Zenyka Viedeyona (Universitas Prasetiya Mulya, 2013)
Teacher’s performance is the main key of school organization’s success. As the key, teachers’ genuineness is highlighted to be the most demanding of the school operations. They are actors, patrons, front liner workers, and models for the future. It shows that the role of teachers is the center of school operations. In the same situations, school operations are affected by school culture and quality management practices that enhance the teachers to do their duties properly. Teachers’ performances are tied to the culture and total quality management practices of the schools. The purpose of this research is to elaborate the relationships between implementation of total quality management practices, organizational culture and teacher’s performance. The research results indicate that there is a strong relationship between total quality management practices and teacher’s performance. Also there is a moderate relationship between organizational culture and teacher’s performance. While the relationship between total quality management and oganizationa culture is moderate relationship. Both total quality management practices and organizational culture positively and significantly affect teacher’s performance.